Inhibiting ferroptosis mitigates sheep sperm freezing damage - Hai, Erhan; Li, Boyuan; Song, Yukun; Zhang, Jian; Zhang, Jiaxin (Frontiers in Veterinary Science, 2025)
ObjectivesTo evaluate the roles of apoptosis and ferroptosis in cryopreservation-induced damage to sheep sperm, with a focus on assessing the effectiveness of inhibitors targeting these pathways.MethodsInitial analysis compared the expression of apoptotic marker Cleaved-caspase3 (CL-caspase3) and ferroptotic marker Transferrin receptor (TFRC) between fresh and cryopreserved sheep sperm. Elevated CL-caspase3 expression and sustained high TFRC expression post-cryopreservation suggested concurrent occurrence of apoptosis and ferroptosis. Consequently, the study employed Deferoxamine Mesylate (DFO), ferrostatin-1 (Fer-1), liproxstatin-1 (Lip-1), and the apoptosis inhibitor Z-VAD-FMK (Z-VAD) at concentrations ranging from 0 to 10 μM. Post-thaw assessments encompassed plasma membrane integrity, acrosome integrity, and ferroptosis biomarkers. Additional experiments were conducted to measure the expression of GPX4, a key regulator of ferroptosis.ResultsOptimal concentrations (2 μM for DFO, Fer-1, and Lip-1; 5 μM for Z-VAD) significantly improved sperm motility and membrane integrity. Among these, Fer-1 demonstrated the greatest efficacy, reducing reactive oxygen species (ROS), lipid peroxidation, and Fe2+ levels. Z-VAD primarily decreased ROS but was less potent than ferroptosis inhibitors. Notably, Glutathione Peroxidase 4 (GPX4) expression was reduced post-cryopreservation, while Fer-1 supplementation restored its levels to those comparable with fresh sperm.ConclusionBoth apoptosis and ferroptosis play critical roles in sheep sperm cryopreservation. Fer-1 effectively enhanced cryopreservation outcomes by inhibiting ferroptosis, as evidenced by the restoration of GPX4 expression and improvement in sperm quality indicators. These findings highlight ferroptosis inhibition as a promising strategy for preserving genetic material, with implications for animal breeding and biodiversity conservation.